2003
DOI: 10.1001/archpsyc.60.4.377
|View full text |Cite
|
Sign up to set email alerts
|

A 21-Year Longitudinal Analysis of the Effects of Prenatal Alcohol Exposure on Young Adult Drinking

Abstract: Prenatal alcohol exposure is a risk factor for the development of drinking problems in humans. Potential mechanisms for the role of fetal exposure and the development of alcohol problems deserve study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
159
1
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 302 publications
(170 citation statements)
references
References 45 publications
(53 reference statements)
4
159
1
4
Order By: Relevance
“…Animal research has also emphasized that prenatal exposure to the drug represents a critical factor when considering subsequent ethanol affinity as operationalized through exacerbated drinking, active behavior in search of the drug coupled with heightened sensitivity to its reinforcing effects as well as those centrally exerted by its main metabolite (acetaldehyde) [8][9][10][11]. These phenomena have also been reported in human epidemiological studies even when controlling for other variables known to affect ethanol use and abuse (e.g., genetic predisposition as assessed through family history of alcoholism, gender, co-use of other drugs during pregnancy and different environmental factors) [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 91%
“…Animal research has also emphasized that prenatal exposure to the drug represents a critical factor when considering subsequent ethanol affinity as operationalized through exacerbated drinking, active behavior in search of the drug coupled with heightened sensitivity to its reinforcing effects as well as those centrally exerted by its main metabolite (acetaldehyde) [8][9][10][11]. These phenomena have also been reported in human epidemiological studies even when controlling for other variables known to affect ethanol use and abuse (e.g., genetic predisposition as assessed through family history of alcoholism, gender, co-use of other drugs during pregnancy and different environmental factors) [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 91%
“…Like nicotine, alcohol readily crosses the placenta and the blood-brain barrier (Julien 1998), and like nicotine, prenatal alcohol appears to predispose offspring to subsequent drug use (Baer et al 2003;Spear and Molina 2005;Yates et al 1998). Furthermore, accumulating evidence indicates that alcohol may interact directly or indirectly with neuronal nicotinic cholinergic receptors (nAChRs; Dani and Harris 2005;) and nicotine affects multiple actions of EtOH on dopaminergic reward and locomotion behaviors (Blomqvist et al 1992;Larsson et al 2002;Soderpalm et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated an increased incidence of substance-abuse disorders in patients with FASDs (Grant et al, 2013;Streissguth et al, 2004). Regarding alcohol-related problems, it has been reported that PAE predicts problems with alcohol in offspring at 14 and 21 years of age (Baer, Barr, Bookstein, Sampson, & Streissguth, 1998;Baer, Sampson, Barr, Connor, & Streissguth 2003). Yates, Cadoret, Troughton, Stewart, & Giunta (1998) examined the impact of PAE on substance dependence in a study with adoptees.…”
Section: Reward Pathwaysmentioning
confidence: 99%